Kajian Fisiologis Status Kalsium Puyuh (Coturnix Coturnix Japonica) setelah Pemberian Cahaya Monokromatik - Kasiyati, Kasiyati; Kusumorini, Nastiti; Maheshwari, Hera; Manalu, Wasmen (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
Deposited calsium makes of the eggshell is influnce of the light. The objective of the study was evaluate exposed of monochromatic light to obtain basic information of the physiology aspect of calcium satus in the quail which direct relation with quality of the eggshell. Two hundred and seventy quails were divided into nine treatments of light, with ten replications and three quails in each replication. The treatments were without light, controls with 15 and 25 W, red, green, and blue lights with intensities of 15 and 25 lux. Control treatment used incandescent bulb. The red, green, and blue lights were provided by light emitting diodes (LED). All lights treatment were given for 14 h daily, started from 17.00 to 07.00. Parameters measured were serum calcium concentrations, calcium contents in bone and the eggshell, weights and thichness of the eggshell. The data obtained were analyzed by analysis of variance (ANOVA), and the differences between treatments groups were subjected for Duncan’s Multiple Range Test (DMRT). All of the data analyzed were done GLM (general linear model) procedure in the SAS program. Quails exposed to monochromatic light had higher serum calcium concentrations and calcium contents in bone (P<0,05). Blue light could be used to increase quality of the eggshell.